UJI TERAP PEMBANGKIT LISTRIK TENAGA AIR SKALA PICOHYDRO DI KABUPATEN BANJARNEGARA - Rachman Djamal; Tri Risandewi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
This study aims to determine the technical application of picohydro power plant (making design and application test) in Pandansari Village, Wanayasa District, Banjarnegara Regency. The result of technical analysis of picohydro power plant is capable of producing 7.200 watt or 7,2 kilowatts of electric power. Based on the observation and calculation of water discharge in July-August 2017, the water debit required to run the generator on picohydro power plant is insufficient (less than 30 liters / sec) due to the months already entering the dry season in Banjarnegara Regency and also because some of the water debit is used by waterwheel to increase water supply to the water container / reservoir belonging to the people of Pandansari Village. During the dry season, the picohydro power plant can be used when operated alternately with a water mill or set the time of use for each water mill used in the morning until late afternoon, while the picohydro power plant is used during the afternoon until night or early morning when people need electricity for their daily needs. The next alternative is to place a second picohydro / turbine generator under the first turbine utilizing waste water from the first turbine with a height difference of at least 2 meters or more. If during the rainy season, there is a very heavy flow of water from above then the overflow can be disbursed / dumped down through the overflow channel so that the performance of the picohydro generator is not disturbed